Estimation of material properties using magnetic resonance imaging - Lee, Xue Fen. (2010)
Osteoporosis is a metabolic disease that does not have any symptom until a fracture occurs. The current assessment of osteoporosis is based on the measure of the bone mineral density. However, it has been known that the trabecular bone microarchitecture has contributed to the bone strength. In this project, Magnetic resonance imaging (MRI) had been used as a non-invasive technique to assess trabecular bone micro-structure. From the images, histomorphometric (structural) parameters were derived to study the trabecular bone microarchitecture. The structural anisotropy characteristic of the trabecular bone was investigated using the structural parameters derived from human MR images and the results showed that there were significant difference (p<0.05) in three orthogonal directions. Correlation studies were carried out using 18 cylindrical bone samples from pig distal femur. Whole pig femurs were scanned using 3T MR scanner with PD sequence. The results derived from MRI were correlated with that from CT, DEXA and mechanical testing. Moderate correlation was found between trabecular thickness computed from MR and CT (R2>0.5). R2 >0.5 was found in CT number against MR trabecular number and spacing (R2=0.5026 and 0.5005 respectively). The MR trabecular number and spacing were also slight correlated to mechanical properties and BMD. However, these two MR parameters were related to mechanical properties and BMD significantly (p<0.05). MRI is able to give structural information of trabecular bone in order to observe the structural changes and predict the bone strength. Therefore, the potential of MRI technique in the assessment of osteoporosis has to be considered.